EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASISTED INDIVIDUALIZATION BERBANTUAN MEDIA LINGKUNGAN SEKITAR DALAM PEMBELAJARAN IPAS MATERI MAKHLUK HIDUP DAN LINGKUNGANNYA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS lV SEKOLAH DASAR - Malaka, Miranti; Fanpada, Nehemia; Bekata, Halena M.; Sanjaya, Ferdino Wedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of students in Science and Social Studies (IPAS) learning on the topic of living things and their environment. The purpose of this study was to determine the effect of the Team Assisted Individualization (TAI) cooperative learning model assisted by environmental media on students' learning outcomes. This study employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest design. The participants consisted of 37 fourth-grade students. The research instrument was a learning achievement test consisting of pretest and posttest questions. Data were analyzed using the Kolmogorov-Smirnov normality test and the Wilcoxon Signed Ranks Test. The results showed that the average pretest score of the students was 49.19, which increased to 81.65 in the posttest. The Wilcoxon Signed Ranks Test revealed an Asymp. Sig. (2-tailed) value of 0.000, which was lower than the significance level of 0.05. These findings indicate that the implementation of the Team Assisted Individualization (TAI) cooperative learning model assisted by environmental media had a significant effect on students' learning outcomes. In addition, the questionnaire results showed positive student responses toward the implementation of the learning model, with an average percentage score of 87%, categorized as strongly agree. Based on these findings, the Team Assisted Individualization (TAI) cooperative learning model assisted by environmental media is effective in improving students' learning outcomes in Science and Social Studies (IPAS) learning on the topic of living things and their environment.